Financial Management as a Tool for Achieving Stable Firm Growth - Saksonova Svetlana; Savina Svetlana (Economics and Business, 2016)
The purpose of this study is to show that financial management in the firm is a tool for achieving stable firm growth and long-term firm stability while problems in firm financial management lead to the inability of firms to ensure sustainable growth of their value.